2020
DOI: 10.21873/anticanres.14690
|View full text |Cite
|
Sign up to set email alerts
|

Novel Prognostic Implications of Methylated RNA and Demethylases in Resected HCC and Background Liver Tissue

Abstract: Background/Aim: N6-Methyladenosine (m6A), the most abundant internal modification of RNA, plays a critical role in cancer development. However, the clinical implications of m 6 A in hepatocellular carcinoma (HCC) remain unclear. Materials and Methods: We analyzed 177 HCC and paired noncancerous liver tissues from patients who underwent hepatectomy according to global m 6 A quantification and expression of m 6 A demethylases fat mass and obesity-associated protein (FTO) and alpha-ketoglutarate-dependent dioxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Several studies reported the increased ALKBH5 in HCC based on TCGA dataset [ 20 , 21 ] while other reports indicated decreased ALKBH5 in HCC [ 22 , 23 ], suggesting ALKBH5 might function differently in different HCC background (such as HBV versus non-HBV related HCC). To define ALKBH5 expression pattern in HBV-HCC, we collected 20 pairs of tumor and peri-tumor tissues with HBV infection history from Chinese patients.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported the increased ALKBH5 in HCC based on TCGA dataset [ 20 , 21 ] while other reports indicated decreased ALKBH5 in HCC [ 22 , 23 ], suggesting ALKBH5 might function differently in different HCC background (such as HBV versus non-HBV related HCC). To define ALKBH5 expression pattern in HBV-HCC, we collected 20 pairs of tumor and peri-tumor tissues with HBV infection history from Chinese patients.…”
Section: Resultsmentioning
confidence: 99%
“…FTO mRNA levels were reported to be significantly lower in HCC tissues. The expression of FTO was reduced in the HCC cells and was closely associated with AFP levels, tumor size, metastasis and vascular invasion 30 , 31 . Another study demonstrated that overexpression of FTO was associated with poor prognosis in HCC patients.…”
Section: The Roles Of M6a Modification In Hccmentioning
confidence: 99%
“…ALKBH5 expression in HCC tissues was significantly lower than that in normal tissues, and the absence of ALKBH5 predicted poor overall survival and disease-free survival in HCC patients [30,35]. ALKBH5-mediated m6A demethylation resulted in the posttranscriptional repression of LY6/PLAUR domain 1 (LYPD1), which could be stabilized by the m6A "reader" IGF2BP1.…”
Section: Alkbh5 and Hccmentioning
confidence: 99%
“…METTL3 is a biomarker of poor prognosis, and the abnormal upregulation of METTL3 expression in HCC results from CNV and DNA methylation rather than somatic mutation [ 116 ]. The low-expression of demethylases (mainly FTO and ALKBH5) and concomitant m6A modifications in noncancerous peritumoral liver tissues are believed to enhance the malignant potential of liver cancer after resection [ 117 ]. Overall, the main m6A regulatory factors related to HCC are YTHDF2, YTHDF1, METTL3, KIAA1429 and ZC3H13.…”
Section: Introductionmentioning
confidence: 99%